Resveratrol derivative‐rich melinjo seed extract induces healing in a murine model of established periodontitis. Issue 5 (31st May 2018) - Ikeda, Eri; Ikeda, Yuichi; Wang, Yongqiang; Fine, Noah; Sheikh, Zeeshan; Viniegra, Ana; Barzilay, Oriyah; Ganss, Bernhard; Tenenbaum, Howard C.; Glogauer, Michael
Abstract: Background: Products of internal defense systems, like pro‐inflammatory cytokines, reactive oxygen species, and leukocytes, are released which attack periodontal bacteria in periodontitis, but at the same time, lead to tissue destruction as well. We hypothesize that resveratrol derivative‐rich melinjo seed extract (MSE), an edible plant extract that has antioxidant properties, should promote healing of periodontal bone loss and modulating immune‐inflammatory systems that leads periodontal tissue destruction. Methods: We used an experimentally induced periodontitis (EP) model in mice. Ligatures were placed first for development of EP (15 days). MSE was intraperitoneally administrated (0.001% (w/w)) to reverse bone loss that had already occurred in established EP and mice were then sacrificed (day 17, 20 and 22). Results: Morphometric outcomes revealed lower bone‐loss in the MSE groups compared to control. Immunohistochemistry assays demonstrated lower oxidative stress in MSE groups. MSE also inhibited M‐CSF/sRANKL mediated osteoclast formation and down‐regulated osteoclast activity. Conclusions: Treatment with MSE in EP actually caused healing of bone, and these effects are probably related to decreases in local oxidative damage and osteoclast activity. Given MSE's positive effects on osteodifferentiation as well, these findings suggest that MSE could be a useful therapeutic agent for the management of periodontitis.